Validation of mobile in situ measurements of dairy husbandry emissions by fusion of airborne/surface remote sensing with seasonal context from the Chino Dairy Complex. (November 2018) - Leifer, Ira; Melton, Christopher; Tratt, David M.; Buckland, Kerry N.; Chang, Clement S.; Frash, Jason; Hall, Jeffrey L.; Kuze, Akihiko; Leen, Brian; Clarisse, Lieven; Lundquist, Tryg; Van Damme, Martin; et al.
Abstract: Mobile in situ concentration and meteorology data were collected for the Chino Dairy Complex in the Los Angeles Basin by AMOG (AutoMObile trace Gas) Surveyor on 25 June 2015 to characterize husbandry emissions in the near and far field in convoy mode with MISTIR (Mobile Infrared Sensor for Tactical Incident Response), a mobile upwards-looking, column remote sensing spectrometer. MISTIR reference flux validated AMOG plume inversions at different information levels including multiple gases, GoogleEarth imagery, and airborne trace gas remote sensing data. Long-term (9-yr.) Infrared Atmospheric Sounding Interferometer satellite data provided spatial and trace gas temporal context. For the Chino dairies, MISTIR-AMOG ammonia (NH3 ) agreement was within 5% (15.7 versus 14.9 Gg yr −1, respectively) using all information. Methane (CH4 ) emissions were 30 Gg yr −1 for a 45, 200 herd size, indicating that Chino emission factors are greater than previously reported. Single dairy inversions were much less successful. AMOG-MISTIR agreement was 57% due to wind heterogeneity from downwind structures in these near-field measurements and emissions unsteadiness. AMOG CH4, NH3, and CO2 emissions were 91, 209, and 8200 Mg yr −1, implying 2480, 1870, and 1720 head using published emission factors. Plumes fingerprinting identified likely sources including manure storage, cowsheds, and a structure with likely natural gas combustion. NH3 downwind of Chino showed a seasonal variation of a factor of ten, three times larger than literature suggests. Chino husbandry practices and trends in herd size and production were reviewed and unlikely to add seasonality. Higher emission seasonality was proposed as legacy soil emissions, the results of a century of husbandry, supported by airborne remote sensing data showing widespread emissions from neighborhoods that were dairies 15 years prior, and AMOG and MISTIR observations. Seasonal variations provide insights into the implications of global climate change and must be considered when comparing surveys from different seasons. Graphical abstract: Eight-plume informed (8I) Gaussian inversion model for I-15 downwind (north to south) transect with respect to arbitrary lateral distance ( y ) for A) ammonia anomaly (NH3 ′) and winds ( u ) versus relative northing ( x ). Plume peaks labeled. Arrows show transect features modeled that indicated the six-plume uninformed model (not shown). B) In situ NH3 and u data superimposed on Mako column ammonia (XNH3 ) data for 25 Jul. 2014, 1820-1846 UTC (1020-1046 LT), and the 8I model-projected plumes' origins in the Google Earth environment. Selected transect plume features labeled. White arrows bracket the transect line onto which transect data are projected. Data key on figure. Shown in the Google Earth environment. Image 1 Highlights: Herd size from three different trace gases converge to ±20% of the average value. Seasonality is observed in NH3 and CH4 satellite data, affecting annualized rates. Seasonality must be considered when comparing campaigns in different seasons. NH3 seasonality was 900%; proposed legacy soil emissions, observed in airborne data. Midsummer Chino dairy emissions were 15.7 Gg NH3 yr −1 and 30 Gg CH4 yr −1 . Abstract : Where sufficient information from multiple gases and number of likely sources, high emissions accuracy can be achieved for in situ data plume inversion.